Effect of soiling in bifacial PV modules and cleaning schedule optimization. (15th October 2018) - Luque, Enric Grau; Antonanzas-Torres, Fernando; Escobar, Rodrigo
Highlights: Soiling rate of 0.236%/day is obtained for the bifacial module during experiment. Soiling rate of 0.301%/day is obtained for the monofacial module during the experiment. Soiling rate of 0.0394%/day calculated for the rear side of the bifacial module. Not cleaning the rear side of the bifacial PV system might be a suitable strategy. Abstract: Bifacial photovoltaic (PV) modules and cells can transform solar radiation into electricity from both front and rear sides, unlike traditional solar technologies which can only generate power through the front face. This ability has shown to increase electric output with various levels of increment, depending on parameters such as distance to the ground, distance between modules, and albedo. This power gain characteristic versatility has attracted the industry, gaining both commercial and research interest. Measuring soiling effects in bifacial modules is an important milestone for the technology, since it is an important source of efficiency loss, thus relevant to the industry when evaluating and designing bifacial systems. In this work soiling rates are measured for bifacial minimodules and compared with traditional monofacial minimodules. The experiment was carried out for a period of two months in Santiago, Chile, measuring short circuit current of the minimodules along with the irradiance in the module plane and albedo. Also, a methodology is proposed to distinguish between soiling in the front and rear sides of bifacial modules, with which a mixed integer lineal problem is designed to obtain optimum cleaning frequency under different strategies and conditions for a period of three years, from 2014 to 2016. It is observed that soiling rate in the monofacial minimodule is 0.301%/day, meanwhile a rate of 0.236%/day was measured for the bifacial module. Also, a rate of 0.0394%/day was calculated for the rear side of the bifacial module, roughly 8.8 times smaller than the front side rate. Finally, several optimizations and simulations where performed to see the effects of soiling rate, albedo, rain, cleaning costs and strategy in cleaning frequency of both the front and rear sides of a bifacial PV system.